Prevalence of overweight, obesity, and associated risk factors in healthy female adolescents in Tehran, Iran - Behnaz Abiri; Parvin Sarbakhsh; Mohammadreza Vafa (University Library System, University of Pittsburgh, 2019)
Introduction: Obesity is an important health concern worldwide and is a growing problem in Iran. Adolescent  obesity has a major role in development of adulthood obesity and its complications. The present study was conducted to evaluate the prevalence of overweight, obesity, and associated risk factors in female adolescents living in Tehran, Iran. Methods: This cross-sectional study was carried out among 2,132 female adolescents aged 14-17 years in Tehran recruited between 2017 and 2018. Weight and height were measured and body mass index (BMI) was calculated. Underweight, overweight, and obesity were considered as < 5th, ≥ 85th, and ≥ 95th percentile, respectively, of CDC BMI-for age and sex criteria. Adolescents and their mothers filled in the questionnaires on physical activity, computer use, duration of breastfeeding, total sleep time, and family socioeconomic status. Statistical analysis was performed using SPSS version 22.0 software. P < 0.05 was considered statistically significant. Results: The overall prevalence rates of overweight and obesity were 24.1% and 6.5%, respectively. The prevalences of overweight and obesity were highest in the South District (28.9% and 7.7%, respectively) and were lowest in the North District (19.1% and 5.2%, respectively). There were significant differences in physical activity level (P < 0.001), total sleep time (P < 0.001), duration of breastfeeding (P < 0.01), and daily computer use (P < 0.001) among the four groups (underweight, normal, overweight, and obese). Regarding the socioeconomic status, parental education level and economic status were significantly higher in those who had normal weight compared to other weight groups (in both, P < 0.001). Conclusion: This study showed that overweight and obesity among female adolescents in Tehranhave become a major public health concern. Level of physical activity, computer use, sleep duration, breastfeeding duration, levels of parental education, and economic status were associated with overweight and obesity prevalence.